2015
DOI: 10.1186/s12889-015-2046-1
|View full text |Cite
|
Sign up to set email alerts
|

A cost-utility analysis of cervical cancer screening and human papillomavirus vaccination in the Philippines

Abstract: BackgroundCervical cancer is the second leading cause of cancer cases and deaths among Filipino women because of inadequate access to screening and treatment services.  This study aims to evaluate the health and economic benefits of HPV vaccination and its combination with different screening strategies to find the most optimal preventive strategy in the Philippines.MethodsA cost-utility analysis was conducted using an existing semi-Markov model to evaluate different screening (i.e., Pap smear, visual inspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 28 publications
1
53
0
Order By: Relevance
“…Type 18 was less frequently detected. There was detection of a few Oncogenic HPV types which were not identified in the studies carried out in home country, [23][24][25][26] as highlighted in red in Table VIII, notably types 66,31,59,68 and 56 among Fili-pino expatriates. Among Arab patients in the study, 6 were nationals of UAE and not many published studies available on HPV genotype prevalence in the UAE.…”
Section: Resultsmentioning
confidence: 99%
“…Type 18 was less frequently detected. There was detection of a few Oncogenic HPV types which were not identified in the studies carried out in home country, [23][24][25][26] as highlighted in red in Table VIII, notably types 66,31,59,68 and 56 among Fili-pino expatriates. Among Arab patients in the study, 6 were nationals of UAE and not many published studies available on HPV genotype prevalence in the UAE.…”
Section: Resultsmentioning
confidence: 99%
“…For control model (14) and the set of admissible controls ( ), we can formulate two different optimal control problems using the objective functionals (16) and (17). Here, we prove the existence of solutions for these optimal control problems and we also obtain the optimality system in order to find a numerical approximation of the optimal controls.…”
Section: The Pontryagin Maximum Principlementioning
confidence: 99%
“…Let us introduce the states = ( , , , , ) and the controls = ( 1 , 2 , 1 , 2 , ) and denote the right-hand side of the control model (14) as the vector function ( , , ). For the objective functional (16), the optimal control problem of the HPV epidemic model is min ∈ ( )…”
Section: The Pontryagin Maximum Principlementioning
confidence: 99%
See 1 more Smart Citation
“…A study that evaluated resources in the Philippines found that high screening coverage with visual inspection with acetic acid was the most cost effective strategy. The addition of vaccination is potentially cost effective if administered to 11-year-olds but current costs of vaccination limit this option (Guerrero et al, 2015).…”
Section: Affordabilitymentioning
confidence: 99%